Dalem Kadipaten Ngabeyan: Court Dance Laboratory in 19th Century Surakarta Kingdom - Yudhistira, Naufal Anggito; Suparta, I Made; Buduroh, Mamlahatun; Setyani , Turita Indah (International Journal of Performing Arts (IJPA), 2025)
Dalem Kadipaten Ngabeyan or also known as Dalem Sasana Mulya is one of the royal residences from Surakarta Kingdom, located in Surakarta, Central Java, Indonesia. Dalem Kadipaten Ngabeyan have an important position in Javanese court dance history as a dance laboratory during 19th century. This research tries to understanding Bedhaya-Srimpi Kadipaten Ngabeyan as a part of court dance tradition in Surakarta and also to understanding Dalem Kadipaten Ngabeyan context. This research tries to integrate historiography method with ethno-philology approach, which try to understanding past culture by text. Bedhaya and Srimpi dance that created in Dalem Kadipaten Ngabeyan cannot be separated with Dutch Colonial context in Java during 19th century. The dance itself represent how Surakarta facing cultural trauma caused by long series of war and internal intrigue. In another hand, many dances from Dalem Kadipaten Ngabeyan represent romantic atmosphere and romanticism of Mataram-Surakarta golden era.